Digital Life Balance Scale: Validity and Reliability in the Turkish Context - Fatma Selda Oz Soysal; Egehan Kosar; Mustafa Can Gursesli; Andrea Guazzini; Mirko Duradoni (Human Behavior and Emerging Technologies)
In our increasingly interconnected world, maintaining a healthy balance between online and offline activities is crucial for personal well-being. The Digital Life Balance (DLB) Scale has been introduced to understand the impact of Internet use on well-being, drawing upon the framework of the psychology of harmony and harmonization. This study is aimed at validating and assessing the reliability of the DLB Scale among Turkish university students. A sample of 424 university students (50.7% females, 49.3% males; age range: 20-31 years) participated. The scale was translated into Turkish, and its language validity was ensured through expert reviews. Confirmatory factor analysis supported the construct validity of the scale, effectively measuring Digital Life Balance in the Turkish context. Convergent validity analysis revealed significant correlations between the DLB Scale and measures of well-being and addiction tendencies. The DLB Scale exhibited good internal consistency (Cronbach’s alpha and composite reliability). Test-retest reliability analysis showed consistent responses over a three-week interval. These findings provide empirical evidence for the validity and reliability of the scale, making it a valuable tool for assessing individuals’ perceptions of balance in their online and offline activities.